2014
DOI: 10.3389/fnbeh.2014.00237
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in bodily freezing predict emotional biases in decision making

Abstract: Instrumental decision making has long been argued to be vulnerable to emotional responses. Literature on multiple decision making systems suggests that this emotional biasing might reflect effects of a system that regulates innately specified, evolutionarily preprogrammed responses. To test this hypothesis directly, we investigated whether effects of emotional faces on instrumental action can be predicted by effects of emotional faces on bodily freezing, an innately specified response to aversive relative to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 68 publications
(99 reference statements)
4
49
0
Order By: Relevance
“…This possibility can be investigated by presenting stimuli that have acquired fear associations through classical conditioning during instrumental tasks (191). Such stimuli simultaneously inhibit appetitive approach and promote withdrawal (191193), indicating that tendencies toward approach and avoidance are subject to indirect contextual modulation by conditioned fear stimuli. By increasing the number of aversive Pavlovian influences within the environment, generalization of fear conditioning could theoretically potentiate both effects.…”
Section: Existing Computational Studies Of Trait Anxietymentioning
confidence: 99%
“…This possibility can be investigated by presenting stimuli that have acquired fear associations through classical conditioning during instrumental tasks (191). Such stimuli simultaneously inhibit appetitive approach and promote withdrawal (191193), indicating that tendencies toward approach and avoidance are subject to indirect contextual modulation by conditioned fear stimuli. By increasing the number of aversive Pavlovian influences within the environment, generalization of fear conditioning could theoretically potentiate both effects.…”
Section: Existing Computational Studies Of Trait Anxietymentioning
confidence: 99%
“…Moreover, a recent study by Ly et al (2014) provides evidence that even whole-body approach/avoidance responses were automatically triggered by valenced stimuli. The authors presented gems on the left or right side of the screen which were preceded by a task-irrelevant facial expression.…”
Section: Contrasting Motivational Orientation Vs Evaluative Codingmentioning
confidence: 99%
“…This is relevant as avoidance is the main maintaining and perhaps even causal factor of internalizing symptoms (Craske, ). Recent human work mainly in adults also has shown that prolonged freezing—or poor recovery from an initial freezing response—predicts subsequent instrumental avoidance responses (Ly, Huys, Stins, Roelofs, & Cools, ; Ly et al., ) and is associated with increased internalizing symptoms (Kozlowska et al., ; Niermann et al., ). Therefore, we hypothesized that freezing is adaptive, but that alterations in this defensive response early in life—in the form of longer freezing—will predict increasing levels of internalizing symptoms in childhood to late adolescence.…”
Section: Introductionmentioning
confidence: 99%